High Stakes Testing Cancellation and its Impact on EFL Teaching and Learning: Lessons from Indonesia - Ashadi Ashadi; Margana Margana; Siti Mukminatun; Amrih Bekti Utami (Universitas Negeri Makassar, 2022)
The differential impacts of high stakes testing (HST) on curriculum, pedagogy, students learning, teacher professional development, and equity have been known in the literature, but its cancellation impact is not yet known. Situated in the post cancellation policy in Indonesian education system, this study seeks to explore the impacts of such policy change on schools, teacher pedagogical practices, and students’ English as a Foreign Language (EFL) learning. A multiple case study design was employed in three different high schools involving 3 school leaders, 3 English teachers, and 9 students in semi-structured and group interviews. Their voices were thematically analysed and constantly compared across cases. The results demonstrate shifts on: (i) the individual student’s and school’s reorientation towards their own vision and mission, (ii) curriculum driven and more varied EFL instructional practices, and (iii) more self-regulated learning activities among certain teachers and students. Further and wider scale investigation is required to look deeper on how these shifts occur among larger groups of stakeholders.